Antibiotic susceptibility pattern of Pseudomonas aeroginosa isolated from ready to eat food from selected street vending food locations in Ikpoba-Okha local government area of Edo State - Shadrach Osalumhense Okhuebor; Osazee Izevbuwa (Hasanuddin University, 2021)
This study was conducted to analysis of the antibiotic susceptibility pattern of Pseudomonas aeroginosa isolated from ready-to-eat food in selected street food vendors in Ikpoba-okha LGA. The mean total viable plate counts (TVC) for Pseudomonas aeroginosa was ascertained with the spread plate methods using nutrient agar with results indicating a mean total viable count (TVC) ranging from 2.20 x 10⁵ to 1.05 x 10³. The highest counts of 2.20 x 10⁵ was obtained in food samples collected from SFL 5 while the lowest count of 1.05 x 10³ was obtained from SFL 1. The organism had a high percentage occurrence of 90% haven been isolated from most food samples (especially soups) from all street food vending location except SFL 3.The data obtained from the gram negative antibiotic susceptibility analysis showed that Pseudomonas aeroginosa was more sensitive to Ciprofloxacin (10µg) and Norfloxacin (10µg), sensitive to Gentamycin (10µg), Augmentin (30µg), Amikacin (30µg) and Ceftazidime (30µg) but showed resistance Cotrimoxazole (30µg), Ceftriazone (30µg) and Tetracycline (30µg). The results of this study indicates that most of the ready to eat food samples examined had high contamination of Pseudomonas aeroginosa and hence did not meet microbiological quality standards. Hence, it is recommended that a more close supervision of ready to eat food from street food vending locations in Ikpoba-okha should be carried out by relevant authorities.